ANALYSIS OF FACTORS INFLUENCING TAX AVOIDANCE OF CONSUMER GOODS MANUFACTURING COMPANIES ON THE IDX (2018-2021) - Riskiani, Riskiani; Ayundyayasti, Prima; Christina, Budhi Adhiani (Applied Accounting and Management Review (AAMAR), 2024)
This study aims to investigate the impact of the board of commissioners, audit committee, company size, and leverage as an intervening variable on tax avoidance among manufacturing companies in the consumer industry sector listed on the IDX for the period of 2018-2021. The sample selection was carried out by purposive sampling technique and a sample of 37 companies was obtained with 148 financial report data. The type of research used is quantitative research with secondary data. The study utilized panel data regression analysis and path analysis through Eviews 12. The findings suggest that tax avoidance is negatively impacted by the board of commissioners and company size, while leverage has a positive impact. Moreover, the board of commissioners and audit committee have a negative effect on leverage, whereas firm size has a positive effect. However, the audit committee does not have any effect on tax avoidance. Leverage successfully intervened in the influence of the board of commissioners and the audit committee. However, they were unable to intervene in the company size with regards to tax avoidance.